The Effectiveness of Internal Audit Office’s Roles: Evidence from Indonesia’s State-Owned University - Wulandari, Eva; Rusdi Akbar (Universitas Muhammadiyah Surakarta, 2026)
This study investigates the factors influencing the effectiveness of Internal Audit Office (IAO) in State-Owned University (SOU) in Indonesia. An explanatory sequential mixed method was employed on the data collected from the chairperson or members of the IAO and also management of 31 SOU in Indonesia. PLS-SEM is utilized to analyze the effect of independence, competence, management support, and the relationship between internal and external auditors on the effectiveness of the Internal Audit (IA). Thematic content analysis was used to map the results of interviews with selected participants to explain how the factors affect the effectiveness of the IA. The test results show that competence, management support, and the relationship between internal and external auditors have a significant positive effect on the effectiveness of IA, while independence has no significant effect. The practice of IA at SOU shows the existence of coercive isomorphism in the presence of rules governing the formation and tasks of IA. The existence of encouragement from professional organizations to certify internal auditors in SOU shows the existence of normative isomorphism.